Health care professionals’ opinions and attitudes to addiction - Mutlu, Elif; Bilici, Rabia; Çetin, M. Kemal (Journal of Dependence, 2014)
Objective: The aim of this study is to investigate the alcohol and substance use patterns among health care professionals and to figure out their common opinions and attitudes towards patients with alcohol and substance use.Method: Questionnaires consisting of personal drinking and substance use habits, concepts and social distance towards addiction, opinions about addiction treatment were implied to 1877 health care professionals (doctors, nurses) during a course about “interventions in addiction problem among health care staff” course of Ministry of Health. The data was collected anonymously and has been analyzed with SPSS17.0.Results: Among participants, lifetime alcohol use was 57.9% whereas substance use was reported 3%. The most common illicit substance was cannabis. Benzodiazepines, meperidine and methylphenidate were other substances of choice. The majority of health care professionals were considering addiction as an illness, even the agree with the idea that “addiction is a weakness” (for alcohol 85.23%, substances 87.2%). Persons who had been drinking at least one time alcohol supported the idea that “alcoholism is a mental weakness” more than the nondrinkers (p
Keywords: Health care professionals; addiction; social distance; perception of addiction